2016
DOI: 10.3390/antiox5020016
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Efficacy of Litchi (Litchi chinensis Sonn.) Pericarp Extract in Sheep Meat Nuggets

Abstract: In the present study, the efficacy of litchi fruit pericarp (LFP) extract (0.5%, 1.0% and 1.5% concentration) in retarding lipid oxidation of cooked sheep meat nuggets was evaluated and compared to butylated hydroxyl toluene (BHT, 100 ppm). The total phenolic content and antioxidant potential of LFP extracts were determined. The thiobarbituric acid reactive substance (TBARS) values were evaluated to assess the potential of LFP extracts as natural antioxidants for oxidative stability of cooked nuggets during 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 37 publications
4
33
0
Order By: Relevance
“…Pomegranate fruit peel extracts were found to reduce TBARS values of beef meat ball at refrigerated storage temperature compared to control sample [2]. Extracts from litchi fruit pericarp protected lipid against oxidation in sheep meat nuggets stored for 12 days at 4°C [4]. The present study clearly shows that AFE could be an effective source of natural antioxidant in preventing ground pork against lipid oxidation at refrigerated storage.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Pomegranate fruit peel extracts were found to reduce TBARS values of beef meat ball at refrigerated storage temperature compared to control sample [2]. Extracts from litchi fruit pericarp protected lipid against oxidation in sheep meat nuggets stored for 12 days at 4°C [4]. The present study clearly shows that AFE could be an effective source of natural antioxidant in preventing ground pork against lipid oxidation at refrigerated storage.…”
Section: Resultsmentioning
confidence: 72%
“…Over the years, with increased awareness level among the consumers, the demand for natural antioxidants has increased steadily over synthetic antioxidants in the processed food industry. Recent reports on inhibitory effect of various plant extracts, such as phenolics from pomegranate peel [2], litchi pericarp [4], rapeseed and pine bark [3] on protein and/or lipid oxidation in muscle food system are testimony to this. However, till date, hardly any study has been conducted to investigate the efficacy of Terminalia arjuna ( T. arjuna ; Combretaceae) fruit extract, in retarding lipid and protein oxidation in meat food system, although its leaves, bark, and roots are extensively used as herbal medicine in both traditional Ayurvedic and Yunani systems [5].…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional value of muscle foods may be enhanced by fortifying them with nutrients or nutraceuticals. Furthermore, their quality, shelf life, and safety may be enhanced by treating them with preservatives (such as antimicrobials and antioxidants) that inhibit undesirable chemical reactions or reduce microbiological growth (Das et al., 2016, 2020). For this reason, there has been great interest in developing nano‐enabled systems to encapsulate and deliver these functional ingredients to foods (Choi, Ruktanonchai, Soottitantawat, & Min, 2009; Ferreira & Nunes, 2019).…”
Section: Nanoemulsion‐based Delivery Systems For Muscle Food Applicatmentioning
confidence: 99%
“…The decoctions of Chinese herbal formula containing Litchi seeds were used as indigenous remedies for urologic neoplasms including prostate cancer, bladder cancer, and renal carcinoma (Shi, 2004;Wang, 2011c). Moreover, a considerable amount of studies have shown that in addition to Litchi seeds, the extracts and ingredients from other parts (peels, pulps, and flowers) of Litchi can exert multiple pharmacological actions which have the anti-inflammatory (Das et al, 2016), anti-oxidative (Lee et al, 2016), anti-bacterial (Yang et al, 2016), anti-viral (Gangehei et al, 2010;Xu et al, 2010a), anti-liver injury, and immuneenhancing effects (Noh et al, 2011;Huang et al, 2014a;Yamanishi et al, 2014;Huang et al, 2014b;Huang et al, 2016a;Su et al, 2016;Xiao et al, 2017;Queiroz et al, 2018). Furthermore, there was accumulating evidence indicating that the extracts and compounds from Litchi exhibit anticancer effects by targeting multiple proteins and signal pathways involved in cancer cell proliferation, metastasis, angiogenesis, apoptosis, autophagy, etc.…”
Section: Introductionmentioning
confidence: 99%